Pengembangan Model Kurikulum PAUD Untuk Membangun Kesadaran Disiplin Berlalu Lintas Melalui Pendekatan Seni Musik - Rizal, Hendra; Soeteja, Zakarias S.; Milyartini, Rita (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
Character education should teach kids about traffic discipline from a young age to lower the chance of accidents and help them become more socially responsible. This study seeks to build a cohesive curriculum model for early childhood education centred on character development through music education to promote traffic discipline. The research employed a systematic literature review in accordance with the PRISMA procedure, encompassing the stages of identification, screening, eligibility evaluation, and synthesis. During the identification phase, 633 papers were collected, and following PRISMA selection, 28 peer-reviewed journal articles were synthesised. The synthesis results divided the findings into three groups: (1) traffic discipline and safety (n=4; 14.3%), (2) music learning for character building and discipline (n=14; 50.0%), and (3) early childhood education curriculum and learning device development (n=10; 35.7%). The suggested model combines these three topics into a thematic curriculum that includes goals, fundamental safety knowledge, music tactics (including songs, rhythm, movement, and games), simulation media, and real-life behaviour-based assessment. The synthesis conceptually demonstrates that music contributes to the reinforcement of discipline through structure, repetition, and group coordination. This approach provides a contextual early childhood education curriculum design featuring four observable indications of traffic discipline behaviour: comprehension of regulations, safety accountability, prudence, and compliance with procedural guidelines.